Implementation of the Deep Learning Approach to Improve Islamic Religious Education Learning Outcomes at SMPN 4 Pamekasan - Fitriatul Laila Hasyim; Muliatul Maghfiroh (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Islamic Religious Education learning at SMPN 4 Pamekasan faces problems in the form of students' low ability to understand religious material concepts in depth and a gap between their knowledge and the application of Islamic values in everyday life. This study aims to apply the Deep Learning Approach to improve Islamic Religious Education learning outcomes at SMPN 4 Pamekasan. This study uses a qualitative approach. The subjects of the study were grade IX students of SMPN 4 Pamekasan. Data collection was carried out through observation, interviews, and documentation. Meanwhile, data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The Deep Learning approach is implemented through three main points, namely Mindful Learning (learning with full awareness), Meaningful Learning (meaningful learning that connects material with student experiences), and Joyful Learning (fun learning). The implementation is carried out through case studies of Islamic values, reflective discussions, analysis of moral events, and experience-based projects. The results of the study indicate that the results of the study will be filled in after the data analysis is complete. This study concludes that the Deep Learning approach is effective in improving PAl learning outcomes as a whole, not only in the cognitive domain but also in instilling Islamic values in students' daily behavior